(untitled) (Fiep Bulletin - online, 2014)
This study has put forward the analysis and discussion of sports initiation in Project Social Futsal from Rincão’s Youth Union – UJR, located at the city of Novo Hamburgo – RS, a social sports club, whose aim is futsal practice, using principles regulated by promotion and integration through sport. The methodological paths used were descriptive research and as tools for collecting information, the non- participant observation in lessons of five centers of project Social Futsal and a semi-structured interview with the club’s technical coordinator. It was used the technique of content analysis as a support for the information collected during the period of study. As main conclusions, it was verified that the club tries to use a social-educational methodology when using in its project a sports initiation, which privileges the children’s global learning and the relationship between what happens in class with the life in community with a methodology privileging both the technical-tactical, and the social-educational references. Paradoxically, it presents the competitions as in the traditional models.